Assessment of aortic stiffness during atrial fibrillation: solutions and considerations - Lundwall, Kristina; Al Nouh, Maria; Kahan, Thomas; Spaak, Jonas (Frontiers in Cardiovascular Medicine, 2024)
Background Methods to assess aortic stiffness are not validated during ongoing atrial fibrillation (AF) We aimed to determine whether aortic stiffness can be assessed reliably in patients during AF. Methods and results Carotid-to-femoral and aortic pulse wave velocity (cf/aoPWV), central blood pressure (BP), and augmentation index (AIx) were assessed by a two-site applanation method and a one-site cuff-based oscillometric method in 40 patients with persistent AF and repeated after cardioversion to SR. Mean age was 63 ± 8 years, 73% male, 50% hypertensive. For the two-site method, cfPWV values were slightly higher in AF than in SR (9.3 ± 1.8 vs. 8.5 ± 1.6 m/s, p < 0.001), whereas the one-site method provided similar values in AF and SR (10.1 ± 1.5 vs. 10.0 ± 1.8 m/s).The variability indices from the device was higher in AF for the two-site method (SD 2.5 ± 1.7 vs. 1.0 ± 0.5 m/s, p < 0.001) but similar in AF and SR with the one-site method (SD 0.7 ± 0.2 vs. 0.6 ± 0.2 m/s). Both methods yielded higher central BP (+4.8/+6.6 and +4.1/+5.7 mm Hg) and lower Aix (−6.8 and −9.1 mm Hg) in AF. Conclusions Aortic stiffness can be assessed during AF. Both methods yielded higher central BP and lower AIx in AF, but similar results for PWV in AF and SR, also when adjusted for BP changes. The two-site method showed high variability necessitating repeated measurements. The one-site method showed lower device-calculated variability and needed fewer repeated measurements.